Comparative analysis of quinoa dryers, tray dryer and solar greenhouse type - Mena Reinoso, Angel Patricio; Tuapanta Dacto, Jorge Vinicio (mktDESCUBRE, 2017)
The objective of the research scientific is to evaluate the performance of two kinds of dryers to quinoa, the dryer of trays and the dryer of greenhouse. The project was development in two phases, in the first one the dryer of trays, was use to dry the quinoa of three different samples, one with husk and the other two without it, to three temperatures of 30 °C, 40 °C and 60 °C, with a different humidity in each one. In the second one phase, it was use the dryer solar of greenhouse and double layer, to dry three kinds of samples with the specifications later indicated, except for the temperatures, at different initial humidity and on three different days. The results obtained in the drying of quinoa were adjust to a model of lineal regressions, obtaining an R2 between 0.95 to 0.99 in the two kinds of dryers, resulting in the model that best describes the drying kinetics of quinoa is the Page model, next to the Henderson and Pabis model. Hypothesis testing was done, considering equal variances and it was determine that the best drying performance is obtained in the tray dryer.